2009
DOI: 10.1002/jbm.b.31529
|View full text |Cite|
|
Sign up to set email alerts
|

Physicochemical characterization of biomaterials commonly used in dentistry as bone substitutes—Comparison with human bone

Abstract: The present work focuses on the physicochemical characterization of selected mineral-based biomaterials that are frequently used in dental applications. The selected materials are commercially available as granules from different biological origins: bovine, porcine, and coralline. Natural and calcined human bone were used for comparison purposes. Besides a classical rationalization of chemical composition and crystallinity, a major emphasis was placed on the measurement of various morphostructural properties s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
130
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(146 citation statements)
references
References 47 publications
7
130
0
9
Order By: Relevance
“…It has been shown that physico-chemical properties (like chemical composition and particle morphology) are among the most important factors that influence the material performance in vivo, causing significantly different biological responses [22,[24][25][26][27]. In fact, such properties may change the behavior of macrophages in processes like adhesion, apoptosis, fusion and cytokine secretion [28].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…It has been shown that physico-chemical properties (like chemical composition and particle morphology) are among the most important factors that influence the material performance in vivo, causing significantly different biological responses [22,[24][25][26][27]. In fact, such properties may change the behavior of macrophages in processes like adhesion, apoptosis, fusion and cytokine secretion [28].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Commercial Bio-HAp has been studied by Figuereido et al, fourteen different samples were used in dentistry, three of them based on HAp and the others based on calcium carbonate [11]. Kupiec et al studied the effect of calcination parameters on bone hydroxyapatite in artificial saliva and its biosafety.…”
Section: Introductionmentioning
confidence: 99%
“…hydroxyapatite (HA) are well documented. The in vivo performance of particular brands of alloplastic grafts is often variable [3,8].…”
mentioning
confidence: 99%
“…On the contrary, those with greater Ca/P ratios degrade gradually or not at all and may give rise to remnants that can induce inflammation [2,8]. In addition, lower degradation rates usually result in less new bone formation around the scaffold.…”
mentioning
confidence: 99%
See 1 more Smart Citation